Efecto de borde considerando el gradiente altitudinal en el sendero Los Alisos en el Parque Universitario “Francisco Vivar Castro”, Loja, Ecuador - Vaca Sarango, Maritza Sthefanya (2023)
The Andean forests have an important scenic beauty with potential for tourism in any form, education, and environmental interpretation; However, making natural areas accessible to the public for these purposes causes edge effects, which in turn generate impacts on the biodiversity of the area. The aim of this research was to determine and compare the floristic composition and structure of the vegetation in areas of a trail under edge effect and without edge effect, considering the altitudinal gradient, in the “Francisco Vivar Castro” University Park. 18 transects of 200 m^2 (10 × 20 m) were installed in three altitudinal ranges, following the Los Alisos trail (low, medium, and high area). In each zone, six transects were installed (three with edge effect and three without edge effect); Within each transect, three 5 × 5 m subplots for shrubs were nested. To check the validity of the sampling, the species accumulation curve was determined. All arboreal individuals larger than 5 cm D1.30 m were measured and for the shrub stratum, all individuals found within the 3 subplots were counted. The floristic composition, structural parameters and importance value index (IVI), and the qualitative Sorensen index were determined, moreover, dendrograms were prepared to illustrate the floristic similarity using the BioDiversity Pro 2.0 program. In the area with edge effect, 60 species were recorded within 50 genera and 38 families, with a total of 2 727 individuals. And in the area without edge effect 60 species within 50 genera and 32 families, with 2 521 individuals. The ecologically important species according to the highest IVI, in the area with edge effect were: Alnus acuminata, Piper asperiusculum, Miconia obscura, Palicourea amethystina and Pilea myriantha. In the area without edge effect: Alnus acuminata, Oreopanax rosei, Piper asperiusculum, Nectandra laurel and Miconia obscura. No notable differences were observed in the floristic composition and structure of the vegetation in the two areas with and without edge effect, but in the abundance of individuals, in the areas close to the edge there were more individuals than inside the forest. The altitudinal gradient is a variable that causes important changes in the floristic composition and structure of the vegetation. There is no difference in species richness between the two scenarios studied, the two areas have 73 % floristic similarity; but the difference is observed in the abundance of individuals within the species, being greater in the area with edge effect.